2021
DOI: 10.1016/j.neuropsychologia.2021.107811
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and cognitive overlap between developmental dyslexia and congenital amusia in children

Abstract: Developmental dyslexia and congenital amusia are two specific neurodevelopmental disorders that affect reading and music perception, respectively. Similarities at perceptual, cognitive, and anatomical levels raise the possibility that a common factor is at play in their emergence, albeit in different domains. However, little consideration has been given to what extent they can co-occur. A first adult study suggested a 30% amusia rate in dyslexia and a 25% dyslexia rate in amusia (Couvignou et al., Cognitive Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 124 publications
0
18
0
Order By: Relevance
“…(2008). Furthermore, a sizeable comorbidity between dyslexia and congenital amusia has been observed in adults and children (Couvignou & Kolinsky, 2021; Couvignou et al., 2019). Congenital amusia is characterized by a deficit in music processing and in particular musical STM (Tillmann et al., 2009, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008). Furthermore, a sizeable comorbidity between dyslexia and congenital amusia has been observed in adults and children (Couvignou & Kolinsky, 2021; Couvignou et al., 2019). Congenital amusia is characterized by a deficit in music processing and in particular musical STM (Tillmann et al., 2009, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexic children display lower performance than typically-developing children in recognition STM tasks for pitch (Ziegler et al, 2012) and in tonal recognition tasks from the Primary Measure of Music Audiation (PMMA, Gordon, 1986) as shown by Atterbury (1985) and Forgeard et al (2008). Furthermore, a sizeable comorbidity between dyslexia and congenital amusia has been observed in adults and children (Couvignou & Kolinsky, 2021;Couvignou et al, 2019). Congenital amusia is characterized by a deficit in music processing and in particular musical STM (Tillmann et al, 2009(Tillmann et al, , 2016.…”
mentioning
confidence: 99%
“…It has been firmly established that amusia is not derived from hearing loss, brain damage, or intellectual deficiencies. Only weak associations with dyslexia (Couvignou and Kolinsky 2021 ), syntactic processing in music and language (Sun et al 2018 ), and spatial orientation [14] were found. The study of Couvignou and Kolinsky ( 2021 ) testing 38 dyslecting children by MBAE test has revealed amusia in 34% of the study group versus 5% amusicals in the typically developing children.…”
Section: Phenotypic Description Of Amusiamentioning
confidence: 99%
“…Only weak associations with dyslexia (Couvignou and Kolinsky 2021 ), syntactic processing in music and language (Sun et al 2018 ), and spatial orientation [14] were found. The study of Couvignou and Kolinsky ( 2021 ) testing 38 dyslecting children by MBAE test has revealed amusia in 34% of the study group versus 5% amusicals in the typically developing children. All the mentioned symptoms are only marginally identifiable in amusical subjects.…”
Section: Phenotypic Description Of Amusiamentioning
confidence: 99%
“…Congenital amusia effects about 1.5% of the adult population, and, in addition to the pitch discrimination deficit, is characterized by an inability to recognize familiar melodies, and difficulty identifying when notes in a melody are out‐of‐key (Peretz, 2016; Peretz & Vuvan, 2017; Vuvan et al, 2015). Critically, congenital amusia is not associated with any other hearing disorders; however, recent research has found some degree of comorbidity with dyslexia (Couvignou & Kolinsky, 2021; Couvignou et al, 2019). Moreover, amusia is not due to lack of exposure to music in childhood (Mignault Goulet et al, 2012) and likely has a genetic source (Peretz et al, 2007; Peretz & Vuvan, 2017).…”
Section: Introductionmentioning
confidence: 99%